2022
DOI: 10.1136/bmjspcare-2022-003606
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal OXYGEN therapy

Abstract: ObjectiveTo report data of the use of high-flow nasal therapy (HFNT) in the palliative care setting.MethodsFive hypoxaemic patients were treated by HFNT in a 1-year period in a palliative care setting, either in the last days of life or as part of an intensive treatment for a reversible cause of hypoxic dyspnoea.ResultsFour patients had a similar clinical pattern. After starting HFNT, dyspnoea intensity decreased and oxygen saturation improved, providing a clinical improvement for a duration of 2–3 days, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…From an evidence perspective, HFNT is proven to be an efficient and cost-effective therapy for patients with respiratory diseases, 4 , 5 , 6 , 7 , 8 which is commonly accepted by Spanish physicians as reported in our survey, with 63.2% of the responders acknowledging that they have considered prescribing HFNT. However, our questionnaire also demonstrated that this therapy remains under-prescribed by physicians, showing that administrative issues and lack of communication with the respiratory therapy service providers are the main barriers to the development of at home HFNT in Spain.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…From an evidence perspective, HFNT is proven to be an efficient and cost-effective therapy for patients with respiratory diseases, 4 , 5 , 6 , 7 , 8 which is commonly accepted by Spanish physicians as reported in our survey, with 63.2% of the responders acknowledging that they have considered prescribing HFNT. However, our questionnaire also demonstrated that this therapy remains under-prescribed by physicians, showing that administrative issues and lack of communication with the respiratory therapy service providers are the main barriers to the development of at home HFNT in Spain.…”
mentioning
confidence: 75%
“…High-flow nasal therapy (HFNT) has been shown to be useful in the management of acute respiratory failure, and in chronic respiratory pathology such as stable COPD, 4 , 5 interstitial lung disease, 6 bronchiectasis, 7 and hypoxaemia in palliative care. 7 , 8 The use of HFNT at home is now recognize by the worldwide medical community and was proved to be cost-effective in patients with respiratory failure. 9 , 10 Moreover, two important clinical trials are currently ongoing in Europe to assess the reduction of the occurrence of a second exacerbation (HiFAE), 11 and to evaluate the effect of this therapy on hospital readmission or death (EPiC-HFT) 12 in COPD patients.…”
mentioning
confidence: 99%